Web-Based E-Learning Application For Mathematics And Indonesian Language Subjects At Sman 4 South Tangerang Using Html And Php - Diana, Desy; Ekasari, Munich Heindari (Journal of Renewable Engineering, 2024)
This project develops a web-based e-learning application for Mathematics and Indonesian subjects at SMAN 4 South Tangerang, using HTML and PHP as the main platform. The main goal of this app is to provide interactive and easily accessible educational resources that enhance the learning and teaching process. The app is designed to meet the specific needs of students and teachers, enriching the learning experience through customizable content and interactive features. In this study, we analyzed the effectiveness of the app in terms of increasing student engagement and learning efficiency. The development method involves requirements analysis, system design, implementation, and testing. Usability and accessibility testing is carried out to ensure that the application can be used easily by all students, including those with special needs. The results of using the application show a significant increase in student learning motivation and academic performance, especially in Mathematics and Indonesian. Teachers also reported improvements in classroom management and teaching effectiveness. Despite this, the application still requires some improvements regarding scalability and data security. In conclusion, this e-learning application has been successful in facilitating a more dynamic and supportive learning environment at SMAN 4 South Tangerang. This project offers important insights into how technology can be leveraged to improve the quality of education.